1997
DOI: 10.1897/1551-5028(1997)016<1659:tiofro>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Food Ration on Sediment Toxicity in Neanthes Arenaceodentata (Annelida: Polychaeta)

Abstract: Abstract-A 3 ϫ 2 factorial experiment was conducted to evaluate the influence of food ration on observed toxicity in Neanthes arenaceodentata. Worms were fed one of three food rations: 0.25ϫ, 1.0ϫ, and 6.0ϫ. The 1.0ϫ ration was composed of 4 mg TetraMarin/worm/week and 2 mg alfalfa/worm/week. Worms in each food ration were exposed to one of two sediments: a clean control sediment collected from Sequim Bay, Washington, USA (SC) or a contaminated sediment collected from Black Rock Harbor near Bridgeport, Connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 38 publications
(67 reference statements)
0
30
1
Order By: Relevance
“…It has been used in multiple field studies and individual chemical exposures to spiked sediments (Dillon et al 1993; Green et al 1999; Lotufo et al 2000; Lotufo, Farrar, Inouye et al 2001; Moore et al 2003; Kennedy et al 2004, 2009). The N. arenaceodentata 28‐d test has also been the subject of considerable refinement efforts considering animal age, test duration and food ration (Bridges and Farrar 1997; Bridges et al 1997). For the methods comparison study using California sediments, the N. arenaceodentata test was the second most sensitive test (Figure 3) and more sensitive than the survival test with E. estuarius .…”
Section: Resultsmentioning
confidence: 99%
“…It has been used in multiple field studies and individual chemical exposures to spiked sediments (Dillon et al 1993; Green et al 1999; Lotufo et al 2000; Lotufo, Farrar, Inouye et al 2001; Moore et al 2003; Kennedy et al 2004, 2009). The N. arenaceodentata 28‐d test has also been the subject of considerable refinement efforts considering animal age, test duration and food ration (Bridges and Farrar 1997; Bridges et al 1997). For the methods comparison study using California sediments, the N. arenaceodentata test was the second most sensitive test (Figure 3) and more sensitive than the survival test with E. estuarius .…”
Section: Resultsmentioning
confidence: 99%
“…However, others (Anderson et al, 1998;Bridges et al, 1997;Green et al, 1999) have reported reductions in N. arenaceodentata endpoints, more often expressed for growth than survival, in exposures to contaminated sediments. The 20-d method is documented in a routine testing program (DMMP).…”
Section: Discussionmentioning
confidence: 99%
“…3). Bridges et al (1997) demonstrated that relatively large amounts of supplemental food can reduce the toxicity of test sediments. Also, the 20-d methods use five worms per test chamber (compared to one per chamber in the 28-d method), which may inherently produce greater growth variability because of dominant worm interactions within replicates (Anderson et al, 1998;Bridges et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations